EKINShI TÁRTIPLI BETLIKTIŃ ULÍWMA TEŃLEMESIN ÁPIWAYÍLASTÍRÍW USÍLLARI - Seidullaev, A.K.; Seydullaev, K.X.; Satniyazova, I.Q.; Amangeldieva, J.T. (SCIENCE and SOCIETY, 2025)
This study deals with methods for classifying the general equation of a second-order surface. The work focuses on a methodical approach and includes the application of Lagrange method to reduce the general second order surface equation to a canonical form.